A perspective review of deadly viral diseases: An era of viruses - Sharma, Abhishek; Bhyan, Sarita J.; Malik, Abdul (International Journal of Basic & Clinical Pharmacology, 2021)
This review article overviewed briefly about the era of deadly viruses. Humans have been combating viruses since before our species had even evolved into its recent form. In some cases of viral infections, vaccines and antiviral drugs have allowed us to treat infections from spreading broadly, and have facilitated to patient recover. But it is far from over to fight the viruses. In recent decades, a number of viruses have sprung from animals to humans and have caused massive outbreaks, claiming thousands of lives such as the virus that led to the 2014-2016 Ebola outbreak in West Africa kills up to 90% of the population, making it the deadliest member of the Ebola family. But there are some viruses that are equally deadly, and some are even more deadly. Some viruses, including the novel coronavirus currently undergoing global outbreaks, have a low mortality rate but still pose a serious health risk as we have no means of access to the health facilities and scarcity of resources and infrastructure. Here we are reporting such type of ten deadly viruses. those have infected humans within last 50 years.